A clinical case of meningoencephalitis caused by achlorophyllum aquaticum Prototeca spp. - E. V. Tokareva; T. A. Druzhinina; O. A. Levashova; R. V. Rybas; E. V. Mozharova; Yu. S. Yurmasheva; A. S. Sysoeva (Журнал инфектологии)
Protothecosis is a rare infectious disease caused by non-photosynthetic algae belonging to the genus Prototheca. Its clinical manifestations may be acute or chronic, localized or generalized. In humans, protothecosis is a rare and, in severe cases, highly lethal disease. Protothecosis manifests as three syndromes: skin or soft tissue infection, ulnar bursitis, or disseminated infection, including lesions of the brain membranes and substance (meningoencephalitis).The diagnosis is made on the basis of histologic examination of biopsy material and microbiologic examination of cerebrospinal fluid and affected tissues. In this paper we consider a clinical case of meningoencephalitis caused by the pathogen Prototheca spp. Current literature sources, case history, and data of laboratory examinations of the patient were analyzed.The accumulation of information about this disease, its epidemiologic and clinical features, and identification possibilities will contribute to the verification of the diagnosis, reduction of lethal outcomes, including in patients with chronic diseases and immunodeficiency states.